A pécsi erőmű korszakváltásai - szénfelhasználástól a biomasszáig - Haffner, Tamás (Közép-Európai Közlemények, 2016)
The Pécs Power Plant was plant and built from 1951 to 1965. It burned coal which was mined in the Mecsek Mountaines close to it. The capacity of the power station was increased from 1959 to 1965. After that its output was more than 200 MW. After the Mecsek Coal Mines’ bankruptcy, the power plant acquired Zobák mine and the two other surface mines. After 1995 the Hungarian government started to privatize Hungarian power stations. After two rounds the MVM couldn’t sell the Pécs Power Plant because the government wanted to sell it with the coal mines and the recultivation’s cost scarred off the investors. In the end the American “Croseus Investment Found” bought it with the mines. At the beginning of the 2000’s the power plant stopped to using coal and developed two gas and a biomass use boiler. In 2013 it expended with a straw use boiler. Today the Pécs Power Plant uses only renewable energy resources.